Drivers of Change and Sustainability in Linked Social–Ecological Systems: An Analysis in the Volta River Basin of Ghana, West Africa. Issue 10 (3rd October 2017) - Kotir, Julius H.; Brown, Greg; Marshall, Nadine; Johnstone, Ron
ABSTRACT: Understanding the nature and relative importance of various drivers of change is crucial for sustainable management of natural resources and in prioritizing management efforts, allocating limited resources, and understanding cumulative effects. For this article, we employed structured an expert judgments approach to identify, characterize, and assess the relative importance of the key biophysical and socioeconomic drivers of change within the Volta River Basin, West Africa. Precipitation variability, water availability, land use change, drought events, and population growth were perceived as most important, while biodiversity loss, social conflicts, pest and disease occurrence, urbanization, and pollution were viewed as less critical. A majority of these drivers were characterized as "slow" acting processes as compared to rapidly changing drivers. Intra- and interexpert groups agreement were found to be significant and convergent, indicating the reliability of the results. The implications of these results for sustainable water resources management and agricultural production are discussed.